2020
DOI: 10.1093/pcp/pcaa014
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Responsive Transcription Factor 1 (RRFT1) Is Involved in Extracellular ATP-Regulated Arabidopsis thaliana Seedling Growth

Abstract: Extracellular adenosine triphosphate (eATP) is an apoplastic signaling molecule that plays an essential role in the growth and development of plants. Arabidopsis seedlings have been reported to respond to eATP; however, the downstream signaling components are still not well understood. In this study, we report that an ethylene-responsive factor, Redox-Responsive Transcription Factor 1 (RRTF1), is involved in eATP-regulated Arabidopsis thaliana seedling growth. Exogenous adenosine triphosphate inhibited green s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 74 publications
4
32
0
Order By: Relevance
“…Secondly, the recent hypothesis that apoplast signalling represents a mechanism for collective decision-making in similar fashion to quorum-sensing bacteria identified eATP signalling as a classic example (Chivasa and Goodman, 2019). This study (Zhu et al, 2020) has now raised the possibility of the existence of additional receptor protein(s), which will certainly be subject to future research in addressing these fundamental questions. Extracellular ATP signals via an as yet unknown plasma membrane receptor (which is not DORN1) to activate second messengers, such as Ca 2+ ions, reactive oxygen species (ROS), nitric oxide (NO), and phosphatidic acid.…”
Section: Insights Into Plant Extracellular Atp Signalling Revealed By the Discovery Of An Atpregulated Transcription Factormentioning
confidence: 90%
See 4 more Smart Citations
“…Secondly, the recent hypothesis that apoplast signalling represents a mechanism for collective decision-making in similar fashion to quorum-sensing bacteria identified eATP signalling as a classic example (Chivasa and Goodman, 2019). This study (Zhu et al, 2020) has now raised the possibility of the existence of additional receptor protein(s), which will certainly be subject to future research in addressing these fundamental questions. Extracellular ATP signals via an as yet unknown plasma membrane receptor (which is not DORN1) to activate second messengers, such as Ca 2+ ions, reactive oxygen species (ROS), nitric oxide (NO), and phosphatidic acid.…”
Section: Insights Into Plant Extracellular Atp Signalling Revealed By the Discovery Of An Atpregulated Transcription Factormentioning
confidence: 90%
“…These physiological responses to ATP are thought to arise from altered distribution of auxin. Zhu et al (2020) have now demonstrated that the ATP effects on auxin spatial profiles and root growth are mediated via RRTF1. ATP-induced spread of auxin distribution beyond the quiescent zone (to cortical and epidermal cells) seen in wildtype roots is abolished in loss-of-function rrtf1 mutants.…”
Section: Insights Into Plant Extracellular Atp Signalling Revealed By the Discovery Of An Atpregulated Transcription Factormentioning
confidence: 95%
See 3 more Smart Citations